Finite element analysis of fatigue case studies - Li, Zhengliang (2017)
This project evaluated Stress intensity factor and weld toe magnification factor of a semi – elliptical crack in a single fillet T-joint plate by using ABAQUS XFEM. The effects of crack depth ratio and crack aspect ratio are also investigated. Both stress intensity factor of a plain plate and a plate with welded attachment will be assess using a XFEM method. The magnification factor will be obtained by taking the ratio of the stress intensity factor of a plain plate to a single fillet T-joint plate. The simulation results will be compared with result obtained from BS7910 stress intensity factor equations and weld toe magnification factor equations. Furthermore, several sets of a/c & a/T ratios are used for a better understanding of how the crack geometry will affect the stress intensity factor of the plates.